2015
DOI: 10.17265/2161-6256/2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Melengestrol Acetate as a Strategy to Improve Production Efficiency of Sheep in Rural Areas in Mexico

Abstract: Abstract:The aim of this study was to evaluate the use of melengestrol acetate (MGA) as a strategy to improve the production efficiency in ewes of rural areas in México. Twenty ewes of breeds (Dorper and Dorper with Pelibuey) non-pregnant and with ovarica activity were used. The treatment consisted of the administration of 0.22 mg MGA/ewe/d for 17 d. The MGA efficiency was measured once the treatment finalized, and the producer was responsible for the registration of the estrus presentation and prolificacy rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Pendleton et al (1992) compared the ability of a fluorogestone acetate (FGA) sponge to induce estrus and ovulation in anestrous dairy goats to that of implants containing Norgestomet and concluded that both were equally effective as part of the induction protocol. In small ruminants, the use of such progestogens, such as melengestrol acetate and fluorogestone for these purposes is well-established (Powell et al, 1996;Riesenberg et al, 2001;Rojo-Martínez and Salas-Razo, 2015;Rojo-Martínez et al, 2017). According to Cline at al.…”
Section: Discussionmentioning
confidence: 99%
“…Pendleton et al (1992) compared the ability of a fluorogestone acetate (FGA) sponge to induce estrus and ovulation in anestrous dairy goats to that of implants containing Norgestomet and concluded that both were equally effective as part of the induction protocol. In small ruminants, the use of such progestogens, such as melengestrol acetate and fluorogestone for these purposes is well-established (Powell et al, 1996;Riesenberg et al, 2001;Rojo-Martínez and Salas-Razo, 2015;Rojo-Martínez et al, 2017). According to Cline at al.…”
Section: Discussionmentioning
confidence: 99%